Mantenimiento preventivo y correctivo del centro de computo y su influencia en el rendimiento académico de los estudiantes de la Unidad Educativa Altamira de la ciudad de Santa Rosa durante el periodo lectivo 2011-2012. - Reyes Nagua, Viviana Paola (2013)
This research is of great importance since it is aimed at solving the academic process of students through the correct use of strategies with the implementation of a computer center. The contents find in this thesis are types of computer centers, viruses, problems caused by computer viruses, types of preventive and corrective maintenance, physical and electrical facilities and planning a data center.